Gambaran Tingkat Kepuasan Ibu Hamil sebagai Pengguna Aplikasi ANCY-Care di Kota Yogyakarta - Sari, Okky Nurlita; Widyawati, Widyawati; Lismidiati, Wiwin (Jurnal Kebijakan Kesehatan Indonesia, 2022)
ANCY-Care application (Anemia in Pregnancy-Care), a media that can be used by users  find information about anemia of pregnancy can be accessed with Android-based telephone. In knowing extent to which information systems or media be said succeed, End-User Computing Satisfaction (EUCS) is a method for measuring level of satisfaction of users an application system. The type of research used is descriptive method research with cross-sectional design. The sample in this study were 41 pregnant women who used the ANCY-Care application March-May 2019 in Yogyakarta City. This study used the End-User Computing Satisfaction (EUCS) model instrument that had been translated into Indonesian which had validity and reliability. This research has obtained the ethical feasibility of the research from the Ethics Committee Nursing Faculty of Medicine, Public Health, and Nursing Gadjah Mada University (KE/FK/1365/EC/2018). The overall level of user satisfaction is at an average value of 3.18 while the average value for each EUCS dimension is content dimension 3.12; accuracy dimensions 3.16; format dimensions 3.24; ease of use dimensions 3.20 and timeliness dimension 3.16. Users in generally satisfied in the use of the ANCY-Care application, while for user satisfaction each dimension is at the satisfied level.